Study into the structuralphase transformations accompanying the resourcesaving technology of metallurgical waste processing - Petryshchev, Artem; Braginec, Nikolay; Borysov, Viacheslav; Bratishko, Viacheslav; Torubara, Oleksii; Tsymbal, Bohdan; Borysova, Svitlana; Lupinovich, Svitlana; Poliakov, Anatolii; Kuzmenko, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports a study into the physical-chemical properties of a doped alloy obtained from reduction smelting. That was necessary to identify the parameters that reduce the loss of Ni and Cr when processing oxide alloyed raw materials and utilizing the doping additive received. It was determined that the alloy at Si:C in the charge 0.14–0.50 (O:C=1.78) contains the following phases: a solid solution of C and the alloying elements in γ-Fe and Fe3Si. At Si:C=0.14, it is dominated by a solid solution of C and the alloying elements in γ-Fe with a weakly manifested Fe3Si. A stepwise change of Si:C in the charge to 0.26, 0.38, and 0.50 led to the increased manifestation of Fe3Si. The alloy's microstructure at different Si:C in the charge clearly manifested several phases, with a different content of the basic alloying elements. The content of Ni is 2.97–14.10 % by weight, that of Cr is 0.91‒17.91 % by weight. An increase in Si:C in the charge from 0.14 to 0.50 led to an increase in the content of Si from 0.04 % by weight to 0.55 % by weight. Values for carbon in the examined local areas at the surface of the alloy exposed to X-ray microanalysis ranged from 0.51 to 1.48 % by weight. Local areas of the microstructure with increased Mo (to 9.10 % by weight), Si, and C indicate a possibility of the presence of Mo in the form of silicides or carbosilicides. It follows from the results obtained in the course of our study that the most acceptable Si:C in the charge is 0.26 (at O:C=1.78). In this case, reduction is ensured with a predominance in the phase composition of the solid solution of C and alloying elements in γ-Fe and the manifestation of residual Si in the form of silicides. In other words, we have determined indicators for obtaining an alloy with a relatively low content of Si and C, which is sufficient to provide the required reducing and oxidizing capability of the alloy. This expands the possibilities for resource saving when using the resulting alloy with the replacement of certain part of standard alloying materials when smelting steel brands limited for carbon and silicon.